Expanding emotional capital in court - Nordquist, Cecilia Y.; Bergman Blix, Stina (Frontiers in Sociology, 2022)
This article develops the concept of emotional capital by exposing its operation in proceedings between legal elite professionals. We argue that a) the micro-structural restraints of the interaction order among the participants have to be accounted for in order to understand the dynamics of emotional capital, and; b) the emotional processes at play have to be expanded beyond feelings of care showing how emotions can be employed to reproduce status and power. Empirical examples from criminal courts in Scotland and the United States demonstrate that judges and prosecutors depend on emotional capital to steer the legal proceedings. Emotional capital is both stable in that acquired capital often can be transferred across fields and volatile in that it presupposes interactional agreement to ensure successful emotional capital employment. In contrast, the lack of such agreement may devalue emotional capital regardless of overall capital wealth. In high status positions, the conversion of emotional capital into symbolic capital does not only affect the authority of individual actors but furthermore reproduces public trust in governmental institutions.